Grouper TRADD Mediates Innate Antiviral Immune Responses and Apoptosis Induced by Singapore Grouper Iridovirus (SGIV) Infection - Zhang, Xin; Liu, Zetian; Li, Chen; Zhang, Ya; Wang, Liqun; Wei, Jingguang; Qin, Qiwei (Frontiers in Cellular and Infection Microbiology, 2019)
Tumor necrosis factor (TNF) receptor type 1-associated DEATH domain protein (TRADD) is a TNFR1-associated signal transducer and an essential component of the TNFR1 complex that is involved in activating both apoptotic and nuclear factor (NF)-κB pathways as an adaptor. It also is required for TNFR-1-initiated neuronal apoptosis following in vitro infection with virus as an essential component of the antiviral response. To date, few studies have investigated the function of TRADD in lower vertebrates and its antiviral response to DNA virus infection. In the present study, a TRADD gene (named as EcTRADD) from the orange-spotted grouper (Epinephelus coioides) was cloned and characterized. The full-length cDNA of EcTRADD consists of 1,370 base pairs (bp) and contains a 44 bp 5′-terminal untranslated region (UTR), a 450 bp 3′-UTR including a poly (A) tail, and an 876 bp open reading frame encoding a putative 291 amino acid protein. EcTRADD has two conserved domains of N-terminal domain (TRADD-N) and a death domain (DD). EcTRADD was detected in all examined tissues. EcTRADD was up-regulated in the spleen after infection with Singapore grouper iridovirus (SGIV). Subcellular localization analysis revealed that EcTRADD and EcTRADD-DD exhibited a clear pattern of discrete and interconnecting cytoplasmic filaments resembling the death-effector filaments, while EcTRADD-N was observed in the cytoplasm. After infection with SGIV, EcTRADD, and EcTRADD-DD were transferred to the nucleus. Overexpression of EcTRADD and its domains inhibited replication of SGIV in vitro. Both EcTRADD and EcTRADD-DD induced the caspase-dependent apoptosis in control and infected cells, while EcTRADD-N inhibited the apoptosis. Additionally, EcTRADD and EcTRADD-DD significantly promoted activation of NF-κB and reporter gene p53, whereas EcTRADD-N had no significant effect on p53. The results may provide new insights into the role of fish TRADD in fish virus infection.